Mahkamah Konstitusi Setengah-Hati: Final tetapi Tidak Mengikat dalam Kewenangan Pengujian Konstitusional - Kishan, Marcelino Ceasar; Rauta, Umbu; Alves de Sousa, Freidelino Paixao Ramos (Universitas Widya Gama Malang, 2024)
This article aims to discuss the bindingness of constitutional review decisions of the Constitutional Court of the Republic of Indonesia (MKRI). In particular, this article looks at the relevance between the grand design of the nature of the MKRI decision in Article 24C paragraph (1) The 1945 Constitution of the Republic of Indonesia (UUD NRI 1945) with the practice of constitution disobedience. Based on that issue, this article argues that the MKRI is designed not to have a final and binding decision, but only final decisions. Because based on the Supremacy-of-Text Principle which is coherent with the concept of applying law based on regulations in the Rule of Law, the non-appreance of binding phrases in Article 24C paragraph (1) of the 1945 UUD NRI 1945 makes the decision of the Constitutional Court in the authority of constitutional review has no binding legal force. Grammatical argumentation comes from interpretation with original meaning and textualism methods which find that the word final does not mean binding due the two words stand separately. By drawing on the concepts of strong-form judicial review and weak-form judicial review, the non-binding nature of MKRI decisions can legitimize the disagreement. Because the indecisivenesss of the Constitution establish a half-hearted form of MKRI, namely the partial weak-form judicial review. Thus, the form of MKRI is a strong and weak-form judicial review that makes MKRI decisions can be opposed. This article uses normative research methods with conceptual approach, statutory approach, and comparative approach.